Superficial Keratectomy For The Management Of Cornel Wounds IOn Canines - David Suresh J (Department of Surgery, College of Veterinary and Animal Sciences, 1996)
The present study was undertaken to evaluate superficial keratectomy in the management of experimentally created corneal wounds in canines. The experiment was conducted on sixteen, apparently healthy adult mongrel dogs of either sex, randomly divided into two groups viz., Group I and II, each consisting of eight animals. Under topical anaesthesia using four per cent lignocaine solution, superficial injury on the ventral half of cornea of the left eye was created and after 24 hours, superficial keratectomy was performed on the ventral cornea under general anaesthesia. In Group I, the cornea was protected with the third eye lid flap and temporary tarsorrhaphy whereas in Group II, only tarsorrhaphy was performed to protect the cornea. The animals were premedicated with atropine sulphate (0.04 mg/kg bodyweight) S/C and after five minutes xylazine (0.5 mg/kg bodyweight) i/m. Anaesthesia was induced with five per cent solution of thiopentone sodium i/v. Induction of anaesthesia was complete by 3.34 + 0.28 minutes, duration of surgical anaesthesia was 40.25 + 2.63 minutes and the time taken for recovery was 121.88 + 7.34 minutes. The animals were kept under observation for 30 days. Clinical symptoms exhibited by the animals of both the groups in different postoperative periods were recorded. In Group I, swelling of eye lid, scratching and pawing were observed from the day of surgery upto the sixth postoperative day. Lacrimation was observed upto the ninth postoperative day. In Group II, swelling of eye lid, lacrimation, scratching and pawing were observed upto the sixth postoperative day. In Group I, corneal oedema was present in all the animals from the third postoperative day and in two animals it persisted upto the 12th day. In Group II, five animals had corneal oedema on the third day which persisted upto the sixth day in two animals and in one animal it was seen upto the ninth day. Vascularization in Group I was observed in all the animals on the sixth postoperative day and it persisted upto the 15th postoperative day in three animals. In Group II, vascularization was observed only in two animals between the third and sixth postoperative day. In Group I, third eye lid was found to cover 2/3rd the eyeball on the third day when the sutures were relieved for examination of the cornea and it was found to return to its normal position between ninth day to twelfth day. Congestion of the bulbar and palpebral conjunctivae and third eye lid were noticed between third day and sixth day in all the animals of both the groups. During the postoperative period, the rectal temperature (0 C), pulse rate and respiratory rate did not show any marked variation in both the groups. Lacrimal smear examination on different postoperative period revealed denuded epithelium and cellular debris. Fluorescein dye staining test during postoperative period in both the groups revealed signs of progressive healing of the keratectomy site in all the animals. The keratectomy site in Group I was bright green on the third postoperative day and became fluorescein negative on the ninth postoperative day except in one animal. In Group II, all the animals became fluorescein negative on the ninth postoperative day. The clarity of the cornea at the keratectomy site showed progressive clearing of the cornea during the postoperative period. In Group I, the keratectomy site became crystal clear on 27th day whereas in Group II it became crystal clear on 30th postoperative day. Haemogram during the postoperative period did not show significant variation in the haemoglobin content. The variation in the total leucocyte count and differential leucocyte count were within the normal range in both the groups. The eyeballs were enucleated from two animals each on the fifth, 10th, 15th and 30th day for gross and histopathological evalution. Gross examination of the enucleated eyeballs in Group 1 on the fifth day showed opacity, on the 10th day mild haziness and corneal oedema and on the 15th day, haziness at the keratectomy site. Vascularization of the cornea was noticed in both the specimens collected on the 10th day and in one specimen collected on the 15th day. The keratectomy site appeared crystal clear on the 30th postoperative day. In Group 11, the keratectomy site showed opacity on the fifth day, mild haziness on the 10th day and 15th day. Vascularization of the cornea was noted in both the specimen collected on the 10th day. The keratectomy site appeared crystal clear and lustrous on the 30th day. Microscopical examination of the corneal specimens in Group 1, revealed necrosis of epithelial cells and inflammatory oedema in the epithelium and stroma on the fifth day, epithelial facet formation and fibroplasia on the 10th day, presence of fibrovascular tissue in the stroma on the 15th day and active proliferation of epithelial cells, thickened epithelium and fibroplasia of the stroma on the 30th day. In Group 11, sliding of the wing cells into the wound from its margin were noticed with epithelial facet formation and fibroplasia of stroma on the fifth day, and increased fibroplasia on the 10th day. The corneal epithelium was completely replaced on the 15th day and thickened epithelium with active proliferation of epithelial cells and fibroplasia of stroma was observed on the 30th day specimens.